Impact of Annealing on Optical and Structural Analysis of Chemically Spray-Prepared Nickel Oxide Thin Films - Abbas, Shatha. F.; Ali, Hiba M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In this study, we prepared thin films of nickel oxide with a thickness of 150±10 nm using the pyrolysis spray technique, and their properties were studied for two hours at different annealing temperatures. including (as deposited, 723 and 873) K. Based on XRD measurements, the pattern data showed that (NiO) had an amorphous structure without annealing, but that a cubic polycrystalline structure with a preferred orientation (111), (200), and (220) was produced at a higher annealing temperature. In addition to other techniques, the crystal structure of the film was characterized using X-ray diffraction. The structure and physical characteristics of the NiO thin films are examined using methods based on atomic force microscopy and X-rays. techniques are employed to examine the surface morphology of layers of nickel oxide. As the temperature of annealing increased, the study reported mean diameter, roughness of surface, and particle size mutation values (186.0–254 nm). The wavelength range of (300-1000) nm is also taken into consideration when further examining and reporting transmittance and absorbance spectra, demonstrating various deviations from the nominal values. The results show that a treatment of temperature 873 K produced the sample’s maximum absorbance value. The findings indicate that direct transitions are allowed in the thin films under study at optical energies of (3.57, 3.51, and 3.47) eV, respectively.